Characteristics and Coping Patterns of Young Adult Prostitute Mothers in Kuala Lumpur, and Factors Contributing to their Involvement - Jacob, Rose (2008)
The study describes the characteristics, contributing factors and coping patterns of young adult prostitute mothers in Kuala Lumpur. The study sought to understand this marginalized group whose involvement in prostitution has caused much conflict which has not given them peace within themselves. The study is guided by four research questions: 1) What are the characteristics of young adult prostitute mothers? 2) Why did the young adult prostitute mothers get involved in prostitution? 3) Why did the young adult prostitute mothers continue in prostitution? 4) How did the young adult prostitute mothers cope in prostitution? A qualitative methodology was the research design used in this study. Data was collected mainly through interviews using a semi – structured question interview guide. Five young adult prostitute mothers participated in this study. The main findings emerged from this study have been classified into four categories which are characteristics of young adult prostitute mothers, pushing factors for young adult prostitute mothers involvement in prostitution, continuing factors for young adult prostitute mothers continued involvement in prostitution and coping patterns of young adult prostitute mothers. The study showed that young adult prostitute mothers are just like any other women who are non-prostitutes. Their main concern is to provide care and protection towards their child thus fulfiling their responsibilities as a mother. Conflicts experienced by young adult prostitute mothers encompass religious values, social norms and individual principles. However, to be at peace with themselves, young adult prostitute mothers have identified various strategies to help them cope with their conflicts. The study seems to suggest for policy makers to give attention to an Act for the benefit of this marginalized group. Basic survival needs to young adult prostitute mothers and their children must be looked into by the relevant authorities for their social well being. This study helps the readers and others to understand better young adult prostitute mothers.